2023
DOI: 10.1093/mutage/gead005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genotoxic effect of octyl gallate used as an antioxidant food additive in in vitro test systems

Abstract: Several antioxidant food additives are added to oils, soups, sauces, chewing gum, potato chips etc. One of them is octyl gallate. The purpose of this study was to evaluate the potential genotoxicity of octyl gallate in human lymphocytes, using in vitro chromosomal abnormalities (CA), sister chromatid exchange (SCE), cytokinesis block micronucleus cytome (CBMN-Cyt), micronucleus-FISH (MN-FISH), and comet tests. Different concentrations (0.50, 0.25, 0.125, 0.063, and 0.031 μg/mL) of octyl gallate were used. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, flow cytometry and confocal microscopy analyses using MitoSox or MitoTracker showed that OG also did not reduce either mtROS production or mitochondrial damage (Figure 3b, Supporting Information S1: Figure ). Given that OG is an antioxidant (Avuloglu Yilmaz et al, 2023), we also assessed its impact on ROS production in BMDMs that were stimulated with LPS or LPS + nigericin. Flow‐cytometry analysis using CM‐H2DCFDA showed that OG reduced LPS‐induced but not NLRP3 inflammasome‐induced ROS production of these cells (Supporting Information S1: Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, flow cytometry and confocal microscopy analyses using MitoSox or MitoTracker showed that OG also did not reduce either mtROS production or mitochondrial damage (Figure 3b, Supporting Information S1: Figure ). Given that OG is an antioxidant (Avuloglu Yilmaz et al, 2023), we also assessed its impact on ROS production in BMDMs that were stimulated with LPS or LPS + nigericin. Flow‐cytometry analysis using CM‐H2DCFDA showed that OG reduced LPS‐induced but not NLRP3 inflammasome‐induced ROS production of these cells (Supporting Information S1: Figure ).…”
Section: Resultsmentioning
confidence: 99%